2019
DOI: 10.3390/languages4010013
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Virtual Reality as an Effective Tool for Second Language Vocabulary Learning

Abstract: Learning a second language (L2) presents a significant challenge to many people in adulthood. Platforms for effective L2 instruction have been developed in both academia and the industry. While real-life (RL) immersion is often lauded as a particularly effective L2 learning platform, little is known about the features of immersive contexts that contribute to the L2 learning process. Immersive virtual reality (iVR) offers a flexible platform to simulate an RL immersive learning situation, while allowing the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 58 publications
(96 reference statements)
2
75
0
1
Order By: Relevance
“…The iVR kitchen environment thus conferred more "whole-body" interactive experience to the learner than the iVR zoo, enabling stronger engagement of the sensorimotor system and in turn deriving more embodied representations. Legault et al (13) also noted a trend that learners with higher spatial abilities performed better in the iVR zoo than in the iVR kitchen. Moreover, the authors reported that the iVR features did not impact all learners equally.…”
Section: Individual Differences In Language Learningmentioning
confidence: 93%
“…The iVR kitchen environment thus conferred more "whole-body" interactive experience to the learner than the iVR zoo, enabling stronger engagement of the sensorimotor system and in turn deriving more embodied representations. Legault et al (13) also noted a trend that learners with higher spatial abilities performed better in the iVR zoo than in the iVR kitchen. Moreover, the authors reported that the iVR features did not impact all learners equally.…”
Section: Individual Differences In Language Learningmentioning
confidence: 93%
“…The embodied cognition theory highlights the whole-body interaction with the context, that is, "interaction between perception, action, the body and the environment" 45 , and when engaged, will also activate the brain's perceptual and sensorimotor cortex 46,47 . Although the embodied cognition hypotheses have been examined in many studies of brain and behavior, so far, the focus has been on native L1 speakers; whether and how body-specific and modality-specific experiences play the same role in L2 learning has not received much attention 48,49 . Our SL2 model argues for the important role of social interaction for L2 learning and draws on the link between learning and perception and action, as suggested by the New Science of Learning framework 1 .…”
Section: Theoretical Framework For Understanding the Social Brain Ofmentioning
confidence: 99%
“…Notably, in the present study we capitalized on a CAVE Automatic Virtual Environment (CAVE) system to examine the interaction of language and motor processes during the lexical access of auditory verbs, in the aim of testing the hypothesis that motor representations are part and parcel of the linguistic representations of action verbs (Pulvermüller, 1999). Several studies of language acquisition in adults have demonstrated clear benefits of a virtual environment (Legault et al, 2019;Repetto, Colombo, & Riva, 2015). As concerns the interaction of linguistic and motor processing, Repetto, Cipresso et al (2015) found that simulating actions in a virtual environment facilitated the semantic processing of action verbs that involved the same effector (i.e.…”
Section: Virtual Reality As a Tool To Study Embodimentmentioning
confidence: 99%